Household waste sorting practice, and factors associated with sorting practice in Bedelle town, Southwest Ethiopia. - Dereje Oljira Donacho; Getachew Befekadu Geneti; Mohammed Reshad Kadir; Gutama Haile Degefa; Mukemil Abdella Fugaga (Public Library of Science (PLoS), 2023)
Household solid waste generation rate in low-income countries is increasing due to population growth and changes in people's lifestyles. Sorting waste into categories is an important step in household waste management. However, there is limited information about sorting practices in a low-income setting like Ethiopia. Therefore, this study aimed to assess household solid waste (HSW) sorting practices, and factors associated with sorting practices.A community-based cross-sectional study was conducted from April to May 2021 in Bedelle town. Households were randomly selected, and household heads were interviewed using a pre-tested questionnaire. A total of 209 households were included. The proportion of households that practice waste sorting was calculated. Logistic regression was used to assess the association between HSW sorting practices and associated factors. A P-value of less than 0.05 was declared as significant. The Hosmer and Lemeshow tests were used to check for model fitness.The result of the study shows that the proportion of householders who practiced waste sorting practice in the setting was 21.53%. The sex of the household head, information on sorting benefits, and the availability of private waste collectors for resource recovery were factors in practicing waste sorting at the household level. Accordingly, male-headed households are 88% less likely to practice sorting practice than female-headed households, and those having access to information on waste sorting benefits are 3.68 times more likely to practice sorting, and similarly, households, where private waste collectors are active, are about 4 times more likely to practice waste sorting at the household level than their counterpart. This finding calls on the municipality to create awareness about solid waste sorting practices at the household level, involving both male and female householders in waste management and mobilizing waste collectors at the household level to facilitate effective waste sorting and reuse as sustainable solid waste management options in the town.